Child poverty in the UK since 1998-99: Lessons from the past decade - Mike Brewer; James Browne; Robert Joyce; Luke Sibieta (Institute for Fiscal Studies (IFS), 2010)
As a result of the Child Poverty Act (2010), current and future governments are committed to reducing the rate of relative income child poverty in the UK to 10% by 2020-21. This paper looks in detail at the progress made towards this goal under the previous Labour administrations. Direct tax and benefit reforms are very important in explaining at least three things: the large overall reduction in child poverty since 1998-99; the striking slowdown in progress towards the child poverty targets between 2004-05 and 2007-08; and some of the variation in child poverty trends between different groups of children. However, some of the child poverty-reducing impact of those reforms acted simply to stop child poverty rising as real earnings grew over the period, which increases median income and thus the relative poverty line. The performance of parents in the labour market is important too: between regions, parental employment and child poverty trends are closely related; the overall reduction in child poverty since 1998-99 has been helped by higher lone parent employment rates; and the overall rise in child poverty since 2004-05 has been most concentrated on children of one-earner couples, whose real earnings have fallen.
Keywords: I32; I38; 330; Soziale Lage; Kinderarmut; Großbritannien